Above-ground biomass models for Seabuckthorn (Hippophae salicifolia) in Mustang District, Nepal - Rajchal, R; Meilby, H (Banko Janakari, 2013)
Seabuckthorn (Hippophae salicifolia D. Don.), an important multi-purpose tree, is found at altitudes of 2000–3600 m amsl in Nepal, but so far no models have been developed for estimating the biomass of this species, thus hampering resource assessment and management planning. Hence, the objective of this study was to develop local biomass models for wood, fruit, and leaves of Seabuckthorn. In November 2006, a diameter-stratified sample of 30 trees was harvested in Lete and Kunjo Village Development Committees at an altitude of about 2300 m amsl in the lower part of Mustang District, Nepal. The fresh weight of fruit and oven-dry weight of wood (stem and branches) and leaves were measured and used as a basis for developing biomass models. Diameters of the trees were measured at 30 cm above ground whereas the heights were measured in terms of the total tree height (m). Among several models tested, the models suggested for local use were: ln(woody biomass, oven-dry, kg) = -3.083 + 2.436 ln(diameter, cm), ln (fruit biomass, fresh, kg) = -3.237 + 1.346 ln(diameter, cm) and ln(leaf biomass, oven-dry, kg) = -4.013 + 1.403 ln(Diameter, cm) with adjusted coefficients of determination of 0.99, 0.73 and 0.91 for wood, fruit, and leaves, respectively. The models suggested for a slightly broader range of environmental conditions were: ln (woody biomass, oven-dry, kg) = -3.277 + 0.924 ln(diameter2 × height), ln(Fruit biomass, fresh, kg) = -3.146 + 0.485 ln(diameter2 × height) and ln(leaf biomass, oven-dry, kg) = -4.121 + 0.532 ln(diameter2 × height) with adjusted coefficients of determination of 0.99, 0.68, and 0.92 for wood, fruit, and leaves, respectively. The models can be used in assessment of Seabuckthorn resources and above-ground carbon and in the management of these resources by communities and others. Banko Janakari, Vol. 23, No. 1, Page 23-34 DOI: http://dx.doi.org/10.3126/banko.v23i1.9464